Development of multi‐parameter online monitoring equipment for EHV transformer bushing. Issue 1 (1st January 2020) - Zhang, Lu; Sun, Lei; Wu, Jingfeng; Han, Yanhua; Wang, Sen; Yang, Chuankai; Shen, Wei; Guo, Can
Abstract : To diagnose the running state of bushing and avoid serious power grid accidents, online multi‐parameter monitoring equipment for dissolved hydrogen, oil pressure and temperature in bushing oil was developed. The equipment includes three units: signal acquisition, control cabinet and data analysis. A new hydrogen sensor without oil–gas separation membrane and based on palladium alloy film technology was developed. A three‐in‐one sensor for hydrogen, oil temperature and pressure monitoring has been developed, which has the advantages of miniaturisation, lightweight and easy installation. Test results show the hydrogen measurement range of the sensor is 0–5000 ppm, and the accuracy can reach 10% or 15 ppm (with larger values). The pressure measurement range is 0–1.0 MPa, the resolution is 0.1 kPa, and the accuracy can reach 0.25 grade. The temperature measurement range is −40 to 105°C, and the accuracy is ±1°C. The measurement performance of the device fully meets the requirement of online monitoring of transformer bushing. The equipment has been put into operation in a 330 kV substation, which can monitor the bushing status online and help eliminate the early latent fault of bushing in the weak budding state.